BANKING INNOVATIONS IN THE DIGITAL ECONOMY: TRADITIONAL AND DIGITAL SERVICES OF BANKS - Bakoeva Gulbahor Matyakubovna (European Science Publishing, 2024)
This article aims to understand the complexities of banking innovation in the digital economy. It will build a theoretical framework using established theories and then explore practical aspects through case studies. The research will ultimately provide insights and recommendations to help banks, policymakers, and researchers drive innovation and growth in the digital age.
Keywords: Digitalization, neo banks, trust funds, liquidity, digital economy.